THE SOCIOLOGY OF CULTURAL ASSIMILATION AND SOCIAL INTEGRATION OF IRAQI ETHNIC GROUPS: A CASE STUDY OF SOME IRAQI ETHNIC GROUPS - Sabar, Mohammed Ghazi (Journal of Social Comunity Services, 2026)
Objective: This research aims to study the sociology of cultural assimilation and social integration of Iraqi minorities (Yazidis, Shabaks, Mandaeans) by adopting a mixed methodology that combines quantitative methods (questionnaires and statistical analysis) and qualitative methods (semi-structured interviews). Method: The study utilized a mixed-method approach, employing questionnaires for quantitative data and semi-structured interviews for qualitative insights, complemented by statistical analysis to interpret the findings. Result: The results reveal that cultural assimilation has been clearly achieved through the adoption of the Arabic language and integration into the education system, while structural and political integration remains limited, reflecting a state of ‘incomplete integration.’ The study also highlighted that religious rituals and social ties are effective mechanisms for preserving identity but sometimes reinforce ethnic boundaries. Novelty: The research concluded that overcoming this issue requires comprehensive institutional reforms, including the integration of minority languages into the education system, expanding political representation, and strengthening community networks to ensure greater equity in opportunities for participation and integration.